Fabrication of Conductive 3D Gold‐Containing Microstructures via Direct Laser Writing. Issue 18 (8th March 2016) - Blasco, Eva; Müller, Jonathan; Müller, Patrick; Trouillet, Vanessa; Schön, Markus; Scherer, Torsten; Barner‐Kowollik, Christopher; Wegener, Martin
Abstract : 3D conductive microstructures containing gold are fabricated by simultaneous photopolymerization and photoreduction via direct laser writing. The photoresist employed consists of water‐soluble polymers and a gold precursor. The fabricated microstructures show good conductivity and are successfully employed for 3D connections between gold pads.